BETWEEN DESIRE AND SILENCE: UNDERSTANDING JAPANESE EFL LEARNERS’ WILLINGNESS TO COMMUNICATE IN THE CLASSROOM - Junko Toyoda (PUPIL: International Journal of Teaching, Education and Learning, 2026)
A considerable number of students in university English as Foreign Language (EFL) classrooms remain silent or reluctant to engage in oral communication, a phenomenon widely discussed in EFL research but still under-explored in the Japanese context. To address this issue, the present study investigates, through the lens of the L2 Willingness to Communicate (WTC) framework, the extent to which and the reasons why certain Japanese EFL learners remain silent in class. Using a mixed-methods design, momentary classroom L2 WTC was measured via the Experience Sampling Method (ESM) across five sessions in four English classes, complemented by questionnaires and semi-structured interviews with 11 focal participants. Quantitative analyses revealed consistently low levels of classroom WTC across all sessions. Qualitative data indicated that although students expressed a desire to use the L2 and actively engaged in L2 communication outside the classroom, several classroom factors—such as peer norms, task difficulty, and accuracy-oriented beliefs—continued to constrain their L2 WTC in class. The findings highlight the importance of pedagogical support that addresses situational and psychological barriers to promote more active L2 communication in EFL classrooms.